PENERAPAN METODE PEMBELAJARAN MOTORIK PADA ANAK USIA DINI DI RA DWP IAIN PALU - Kasmiati, Kasmiati (Musawa: Journal for Gender Studies, 2019)
Gross motor development in children is one of the important aspects that need to be considered by educators and parents. Children who have good gross motor skills will make it easier to get along with their friends. The children will be able to be good in the association. This research was used Class Action Research (CAR) approach by describing the motor learning process. The data collection was used observation and documentation. The rubric of children assessment contains 3 aspects of balance, Jumping (strength), and body agility, using 4 categories there are: Very Good Developing (VGD), Developing as Expected (DE), Starting to Develop (SD), Not Developing (ND), Data analysis is carried out from observations obtained through observation sheets in cycles I and II, after the data collected is to analyzed qualitatively to find out the process of action, then the data is processed using presentation techniques, the processed results are then analyzed descriptively to determine the presentation of the success of the action. The results shows that based on data analysis the results of the discussion that through motor learning methods can improve children's gross motor skills, in Pre-Action, The body balance aspects of the children, the category for VGD 10%, DE 10%, SD 5%, and for ND 30%. The strength aspects the body of children, the category for VGD 5 %, DE 15%, SD 20%, and for ND 30%. The body agility aspects for children, the category for VGD 10 %, DE 15 %, SD 1 %, and for ND 50%. After taking action using APE in cycle I, the child's gross motor ability increased, the child increased even though it was not as expected. By finished all the weaknesses in cycle I, the action is continued to cycle II, and the results of observation in cycle II show there is a good improvement, The body balance aspects of the children VGD categories 30%, DE 45%, SD 15%, ND 10%, The strength aspects the body of childres, VGD categories 5%, DE 40%, SD 20%, ND 15 %. The body agility aspects for children,, VGD categories5%, DE 40%, SD 20%, and for ND 15 %. Peningkatan gross motor child of cycle I to cycle II, for VGD categories increased to 11,7%, for DE increased to 13,4%,for SD increased to 1,7%, for ND increased to 7,8 %.